MicroRNA-148a Suppresses Invasion and Metastasis of Human Non-Small-Cell Lung Cancer - Jing Li (Cellular Physiology and Biochemistry, 2015)
Background/Aims: microRNAs (miRNAs) are noncoding RNAs that regulate multiple targets through either the degradation of mRNAs or the inhibition of protein translation, thereby altering several functions simultaneously. Growing evidence indicates that miRNAs are involved in carcinogenesis and tumor progression in non-small-cell lung cancer (NSCLC). Methods: In this study, the mRNA expression levels of miR-148a were examined in NSCLC cell lines and patient specimens using quantitative reverse transcription-PCR. The functions of miR-148a in migration/invasion and lung metastasis formation were determined by using transwell and tail vein injection assays, respectively. Results: We demonstrated that miR-148a was down-regulated in NSCLC metastatic samples, and its expression was suppressed in NSCLC compared with the corresponding nonmalignant lung tissues. Clinical analysis indicated that miR-148a expression was lower in NSCLC patients compared with nonmalignant lung tissues . Decreased miR-148a was significantly associated with tumor node metastasis stage and lymph node metastasis. Furthermore, functional assays showed that miR-148a expression suppressed NSCLC cell invasive and migratory abilities in vitro and suppressed cancer metastasis in vivo, while inhibition of miR-148a enhanced NSCLC cell invasion and lung metastasis formation in a mouse model. Conclusions: Evidence from this study demonstrated that miR-148a exerts tumor-suppressive effects in NSCLC and suggests a new therapeutic option for NSCLC.